Hausmann, F.J., O. Reichmann, H.E. Wiegand en L. Zgusta (Reds.). Worterbücher: Ein internationales Handbuch zur Lexikographie / Dictionaries: An International Encyclopedia of Lexicography / Dictionnaires: Encyclopedie internationale de lexicographie. - Swanepoel, Piet (Lexikos, 1997)
Review of Hausmann, F.J., O. Reichmann, H.E. Wiegand en L. Zgusta (Reds.). Worterbücher: Ein internationales Handbuch zur Lexikographie / Dictionaries: An International Encyclopedia of Lexicography / Dictionnaires: Encyclopedie internationale de lexicographie.